Decision Support System Nutritional Supplement Receipt Determination Method Using Simple Additive Weighting (SAW) - Muhammad Irfan Sipayung; Arjon Samuel Sitio (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Nutrition is a component of body builders in order to maintain and repair the tissues so that the function of the body can function properly. Currently in the village broke promontory has run a program providing nutrition food additive in which the program is based as a growth pattern in the village communities are uneven due to the lack of ancestry in consuming foods that are healthy and nutritious. Until now there has been the way of effective work to determine the acceptance of additional nutrients in the village broke headland. This study aims to assist the village in determiningNutritional Supplement acceptance in the village of Tanjung Disconnect. This system is built using a simple method that perogram Additvive weighting that can be done more effectively. Additvive simple weighting method is one method used in decision support seistem prosesperhitungnya by finding the weight values ??for each attribute.